Avaliação de protocolos de aquisição de imagens em PET/CT de corpo inteiro visando à otimização de varreduras - Fernanda Guerra Paiva (2021)
PET/CT has an important role in diagnosis and staging of human disease. It allows the quasi-simultaneous acquisition of anatomic (CT) and functional (PET) information of a patient within a single examination and hence provides hybrid images of the two modalities. Although the immediate benefit to the individual patient may be substantial, relatively high radiation doses associated with PET/CT, compared with conventional exams have raised health care, being one of the more challenging areas of medical radiation protection. This is especially concerning for children, who are more sensitive to radiation-induced carcinogenesis. The aim of this study was to evaluate the absorbed and effective doses in anatomical correspondence to different organs of the human body from a PET/CT examination, using different oncological protocols and phantoms, aiming at the optimization of the practice and, also, mapping the protocols of PET/CT used in Brazil. To evaluate the CT organ doses, radiochromic film strips were correctly positioned into each phantom, in locations corresponding to the desired organs. The calculation of the effective dose from the administered 18F-FDG, the ICRP 106 Biokinetic model was used, in addition to simulations of effective dose using the SNMMI calculation tool. The results show that the doses differ considerably from one organ to another and depend on the phantom and the chosen protocol. Considering the substantial radiation dose of whole-body PET/CT examinations and the potential for wide variation in contributing factors, all aspects of the examination process should be considered for optimization. This is especially important for pediatric patients, since even if the scanning distance is shorter, the effective dose is higher for the first years of life due to the radiosensitivity of the tissues in this age group. The importance of the optimization of tomographic protocols is emphasized, since diagnostic CT is responsible for more than 60% of the effective dose in the patient. In addition, considering that in oncological studies patients undergo a series of control images, a cumulative exposure is generated. Thus, the search for techniques that allow the reduction of absorbed dose has great relevance. The mapping of the protocols used in the country highlights that most clinics choose to perform anatomical mapping CT images. The consolidation of a dynamic culture in radiological protection must be disseminated throughout the country.